2021
DOI: 10.1055/a-1497-6532
|View full text |Cite
|
Sign up to set email alerts
|

Monitored needle acceleration in endoscopic ultrasound-guided fine-needle aspiration of solid pancreatic masses improves sample quality and diagnostic accuracy: a randomized trial

Abstract: Background and study aims. EUS FNA is recommended for diagnosis of solid pancreatic masses. We aimed to evaluate if a high needle movement acceleration value during puncture increases diagnostic accuracy. Patients and methods. EUS FNA needle acceleration was measured using a PocketLab accelerometer connected by Bluetooth to a smartphone. Two passes (fast and slow) with higher and respectively lower than 1g needle acceleration values were performed in random order. Sample cellularity and quality were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…When the actual needle speed was measured during EUS-FNA, the diagnostic accuracy and specimen quality were higher when the acceleration was greater than 9.8 m/s 2 . 49 The fanning technique, which is defined as using the needle to sample multiple areas within a lesion using the up/down knob of the echoendoscope, has been introduced, and showed superiority because fewer passes were required to confirm the pathologic diagnosis. 50 The torque technique, which is defined as applying torque by twisting the shaft of the echoendoscope in the clockwise or counterclockwise direction without using the left/right control knob during EUS-FNAB, was evaluated in a prospective study of 124 patients with solid pancreatic masses, and the authors concluded that the torque technique enabled better histologic core procurement.…”
Section: Technical Issues During Eus-guided Tissue Acquisition Techni...mentioning
confidence: 99%
“…When the actual needle speed was measured during EUS-FNA, the diagnostic accuracy and specimen quality were higher when the acceleration was greater than 9.8 m/s 2 . 49 The fanning technique, which is defined as using the needle to sample multiple areas within a lesion using the up/down knob of the echoendoscope, has been introduced, and showed superiority because fewer passes were required to confirm the pathologic diagnosis. 50 The torque technique, which is defined as applying torque by twisting the shaft of the echoendoscope in the clockwise or counterclockwise direction without using the left/right control knob during EUS-FNAB, was evaluated in a prospective study of 124 patients with solid pancreatic masses, and the authors concluded that the torque technique enabled better histologic core procurement.…”
Section: Technical Issues During Eus-guided Tissue Acquisition Techni...mentioning
confidence: 99%
“…Patients are usually discouraged from using their phones in restricted-access hospital areas and doctors may appear unprofessional when using phones during their working activity. Our colleagues from the University of Medicine and Pharmacy of Bucharest have a different opinion: we should instead keep our phones on and have them wirelessly connected to an endoscopic ultrasound (EUS) needle while performing tissue acquisition.In this issue of Endoscopy, Ciocîrlan et al report the results of a prospective trial using a digital accelerometer, which was taped onto an EUS fine needle (EZShot3 plus, 22G; Olympus Corp.) and connected via Bluetooth to the physician's smartphone [1]. A dedicated app was available to trace and show the speed of needle insertion into solid pancreatic tumors of more than 20 mm in size.…”
mentioning
confidence: 99%
“…In this issue of Endoscopy, Ciocîrlan et al report the results of a prospective trial using a digital accelerometer, which was taped onto an EUS fine needle (EZShot3 plus, 22G; Olympus Corp.) and connected via Bluetooth to the physician's smartphone [1]. A dedicated app was available to trace and show the speed of needle insertion into solid pancreatic tumors of more than 20 mm in size.…”
mentioning
confidence: 99%